Metode ocenjevanja dinamičnega ploskega stopala - Novak, Zala (Rehabilitacija (Ljubljana), 2017)
Functional flatfoot is a common condition in infants and children. To date, universally accepted definition of, and evaluation method of the foot arch in children has not been completely established. Existing methods of flatfoot evaluation are based on visual assessment, anthropometric values, footprint parameters and radiographic evaluation. The aim of the article is to present currents methods for paediatric flatfoot assessment and to discuss their advantages and disadvantages in evaluation of medial longitudinal arch development.
Keywords: arch; assessment; Child; dinamično plosko stopalo; Flatfoot; functional flat foot; ocenjevanje; otrok; stopalni lok